Depression common in early pregnancy and correlates with poor quality of life - Singh, Gurmeet (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To look for prevalence of depression in patients with early pregnancy and see the effect of depression on quality of life (QOL). Methods: Patients in early pregnancy with gestational age <12 weeks were enrolled into the study. Depression was assessed with Center for epidemiologic studies depression (CES-D) scale. QOL was measured using the World Health Organization QOL‑BREF (WHOQOL‑BREF). Results: Out of 74 patients were enrolled in the study 51(68%) patients had depression, 52 (70%) had vomiting and 15(20.2%) had unplanned pregnancy. Patients with depression had higher prevalence of vomiting (78% versus 52%, P =0.022) and lower prevalence of unplanned pregnancy (13% versus 34% P=0.037) as compared to patients without depression. Patients with depression had significantly lower scores for physical , psychological and environmental domains of QOL. There was no difference in the age, gestational age, previous preterm delivery, previous miscarriage, previous pregnancies and social domain of QOL between patients with and without depression. Depression score had significant negative correlation with physical (r= -0.588,p<0.001), psychological (r= -0.561, p <0.001) and environmental (r= -0.313, p=0.007) domains of WHOQOL-BREF. Conclusions: Depression is common in patients with early pregnancy and correlates with lower QOL of life. Depressed patients were more likely to have vomiting and poor QOL. Key Words: depression, early pregnancy, quality of life, vomiting.